110 kV substation relay protection. (September 2020) - Feng, Xianjie; Fei, Zejie
Abstract: In this paper, the main electric wiring mode of 110kV substation is selected, the structure of substation is determined, and then the main wiring diagram is drawn. According to the design and load of the primary electrical connection, select the maximum and minimum operating modes to calculate the short circuit separately. Then, according to the short-circuit current parameters, the relay protection of transmission lines, transformers, busbars, etc. is set, and the configured protections include current quick-break protection, gas protection, and longitudinal differential protection. Finally, a comprehensive evaluation of the selected protection devices is carried out. Adding relay protection device in substation can send out fault signal and cut off fault line in time to reduce the occurrence of substation fault, so as to ensure the reliable power supply of users and enterprises.